REPRESENTATION OF LIFESTYLE IN POCARI SWEAT AND COCA COLA ADVERTISEMENTS - MUNFAATI, SAMROTUL (LANGUAGE HORIZON, 2018)
This paper is aimed to analyze people?s lifestyle that is represented through the choice of products based on advertisements. It used two printed advertisements of drink products which were Pocari Sweat and Coca Cola. The ads were then showed to 30 young adults as the participants. The results showed that 20 participants were fond of healthy lifestyle which was portrayed by Pocari Sweat while 10 of the participants felt that Coca Cola represented their lifestyle, in this case western lifestyle as the coke is an American product. Meanwhile, according to viewer reading theory, the participants were divided into three categories. 13 participants were regarded as a preferred reader as they catch the idea that the ad offered while 14 other participants belonged to oppositional reader since they were interested with the ads yet they were not really engaged with the products so it did not affect their choice at all. Lastly, 4 of the participants would like to think further if they face the ads.